Periconceptional Dietary Quality and Metabolic Syndrome at 3 Years Postpartum - Lisa M. Bodnar; Qianhui Jin; Ashley I. Naimi; Hyagriv N. Simhan; Janet M. Catov; Sara M. Parisi; Sharon I. Kirkpatrick (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The period around pregnancy is a critical window in the primordial prevention of cardiovascular disease, but little is known about the role of dietary patterns in cardiometabolic health. Our objective was to determine the association between alignment of periconceptional diet with the 2020 to 2025 Dietary Guidelines for Americans and the risk of metabolic syndrome. Methods and Results We used data from the Nulliparous Pregnancy Outcomes Study: monitoring mothers‐to‐Be Heart Health Study, a pregnancy cohort study that followed pregnant participants to a median of 3 years postpartum (n=4423). Usual dietary intake in the 3 months around conception was estimated from a Food Frequency Questionnaire. Alignment with the Dietary Guidelines was measured using the Healthy Eating Index‐2020, where higher scores represent greater alignment. Postpartum metabolic syndrome was defined using the American Heart Association/National Heart, Lung, and Blood Institute guideline. The prevalence of metabolic syndrome at 3 years postpartum was 20%. After adjusting for confounders, the prevalence of metabolic syndrome was flat up to a periconceptional Healthy Eating Index‐2020 total score of ≈60, and then declined steeply as scores increased. Compared with a Healthy Eating Index‐2020 score of 60, having scores of 70, 80, and 90 were associated with 2, 4, and 7 fewer cases of metabolic syndrome per 100 individuals, respectively (prevalence differences: −0.02 [95% CI, −0.03, 0]; −0.04 [−0.08, −0.1]; −0.07 [−0.13, −0.02]). Conclusions Dietary interventions around conception and systems‐level changes to support high diet quality may be important for improving postpartum cardiometabolic health, and helping to reverse or slow the decline in women's cardiometabolic health.